1965
DOI: 10.1042/bj0970318
|View full text |Cite
|
Sign up to set email alerts
|

The species distribution of xanthine oxidase

Abstract: 1. The distribution of xanthine oxidase in blood and tissues of various animals was studied by means of a radioactive assay capable of detecting 10(-7) unit of enzyme. The method was shown to be applicable to tissues with a high uricase content. 2. Of 16 mammalian species examined, six had low concentrations of xanthine oxidase in the serum. In six non-mammalian species, no activity was detected in the serum. 3. The enzyme was not found in the blood cells of any mammals, but was present in the nucleated red bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
85
1

Year Published

1967
1967
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(92 citation statements)
references
References 4 publications
6
85
1
Order By: Relevance
“…• " Xanthine oxidase is relatively low in the whole brain. 12 - 13 However, a recent immunocytochemical study demonstrated the presence of substantial xanthine oxidase in various vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…• " Xanthine oxidase is relatively low in the whole brain. 12 - 13 However, a recent immunocytochemical study demonstrated the presence of substantial xanthine oxidase in various vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…2B) and catalytic activity (Table 1), was observed even under normoxic conditions. Even though rodents have much greater XOR-specific activities in plasma than humans (49), release of this enzyme from XOR-replete human splanchnic tissues can still have potent pathophysiologic effects. Present evidence supports that not only the extent of XOdependent tissue O 2 ⅐Ϫ production, but also its anatomic location, will determine whether or not vascular ⅐ NO-dependent signaling is adversely affected (50).…”
Section: Discussionmentioning
confidence: 99%
“…Infarcts were produced by 40 min of coronary occlusion followed by reperfusion. After the initial surgical preparations but approximately 35 Postmortem studies. Area at risk.…”
Section: Methodsmentioning
confidence: 99%